Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2012
DOI: 10.1145/2207676.2208741
|View full text |Cite
|
Sign up to set email alerts
|

Understanding mobile Q&A usage

Abstract: Recently questioning and answering (Q&A) communities that facilitate knowledge sharing among people have been introduced to the mobile environments such as Naver Mobile Q&A and ChaCha. These mobile Q&A services are very different from traditional Q&A sites in that questions/answers are short in length and are exchanged via mobile devices (e.g., SMS or mobile Internet). While traditional Q&A sites have been well investigated, so far little is known about the mobile Q&A usage. To understand mobile Q&A usage, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…Nam et al [19] found a similar trend in Naver KiN; answerers' participation on Naver KiN is intermittent, and their expertise lower than is in often found in specialized online forums [19]. This trend persists in mobile Q&A [17]. The time it takes for questions to be answered on social Q&A sites tends to be fairly long.…”
Section: User Interactions In Social Qandamentioning
confidence: 89%
See 1 more Smart Citation
“…Nam et al [19] found a similar trend in Naver KiN; answerers' participation on Naver KiN is intermittent, and their expertise lower than is in often found in specialized online forums [19]. This trend persists in mobile Q&A [17]. The time it takes for questions to be answered on social Q&A sites tends to be fairly long.…”
Section: User Interactions In Social Qandamentioning
confidence: 89%
“…Hsieh et al [13] showed that in Microsoft Live Q&A, the average time was almost 3 hours, with 20% of questions never even receiving an answer. The average time in Naver's mobile Q&A was 15.5 minutes, and 34% of the questions were not answered; unlike traditional social Q&A, mobile Q&A users often repeat or refine their information needs over a series of questions as coping strategies [17]. Yang et al [26] studied two-year-long Q&A datasets from multiple social Q&A sites to understand user lifespan and community stability.…”
Section: User Interactions In Social Qandamentioning
confidence: 99%
“…Social media technologies are deeply wired into users' everyday lives, and facilitate soliciting information from one's social connections [9], from online communities [10] and social networks [13], [14]. The affordance of social media ameliorates face-to-face social interaction overload with visual anonymity and time flexibility [11].…”
Section: A the Use Of Social Media For Individuals With Autismmentioning
confidence: 99%
“…Thus, we focused on ten discussion boards (3,4,7,8,9,10,11,12,13,14) in which the forum users discuss their everyday experiences, concerns, and challenges. Using the python library Beatifulsoup4 [22], we collected 1,945 threads (28,960 individual posts) from the discussion board archives over a time period from June 1, 2010 to July 27, 2013.…”
Section: B Data Collectionmentioning
confidence: 99%
“…Panovich, Miller, and Karger (2012) examined the role of tie strength in responses to status message questions on Facebook, while Paul, Hong and Chi (2012) analyzed questions asked on Twitter and found that 42% of questions were rhetorical. Social media question asking in specific communities, such as the blind (Bigham et al, 2010) and mobile phone users (Lee, Kang, Yi, Yi, & Kantola, 2012), has also been a topic of inquiry.…”
Section: Social Network Question Askingmentioning
confidence: 99%